2021
DOI: 10.15585/mmwr.mm7010e1
|View full text |Cite
|
Sign up to set email alerts
|

First Identified Cases of SARS-CoV-2 Variant P.1 in the United States — Minnesota, January 2021

Abstract: has been receiving 100 specimens per week (50 from each of two clinical partners) with low cycle threshold (Ct) values for routine surveillance for SARS-CoV-2, the virus that causes COVID-19. On January 25, 2021, MDH identified the SARS-CoV-2 variant P.1 in one specimen through this surveillance system using whole genome sequencing, representing the first identified case of this variant in the United States. The P.1 variant was first identified in travelers from Brazil during routine airport screening in Tokyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 4 publications
0
20
0
2
Order By: Relevance
“…Cases of P.1 variant infection were observed among travelers arriving in Japan from Brazil on January 2021 [ 57 ]. The first case of the SARS-CoV-2 P.1 variant in the US was identified in Minnesota resident with travel history to the southeastern part of Brazil within the 14 days before symptom onset [ 58 ]. Currently, almost 500 cases of this variant have been reported in the US and it is present in 31 states [ 30 ].…”
Section: Variant Of Concernmentioning
confidence: 99%
“…Cases of P.1 variant infection were observed among travelers arriving in Japan from Brazil on January 2021 [ 57 ]. The first case of the SARS-CoV-2 P.1 variant in the US was identified in Minnesota resident with travel history to the southeastern part of Brazil within the 14 days before symptom onset [ 58 ]. Currently, almost 500 cases of this variant have been reported in the US and it is present in 31 states [ 30 ].…”
Section: Variant Of Concernmentioning
confidence: 99%
“…Just over one year after the initial outbreaks, SARS-CoV-2 continues to spread through populations on all seven continents, resulting in a total of 119,220,681 cases and 2,646,826 deaths (as of March 10th , 2021) [12]. The emergence of new viral variants, such as the B.1.1.7 variant, further complicates efforts to contain the virus and raises important questions about the efficacies of approved vaccines that were developed against the original viral isolate [13]. The COVID-19 pandemic continues to be the cause of considerable morbidity, mortality, socio-economic burden and brings acute attention to the disruptive potential of emerging pathogenic viruses and the urgent need to find new methods for stopping them [4,5].…”
Section: Global Health Challenges and Economic Burdensmentioning
confidence: 99%
“…Others have shown that challenge by the intranasal route results in virus replication in the lungs, heart, brain, kidneys and gut (31,32) with titers increasing over 2-3 days and then subsiding after day 5 in most tissues, but with titers in the brain continuing to rise to >10 8 pfu/g tissue. The latter is thought to result in severe symptoms, which may not be relevant to human disease outcomes.…”
Section: In Vivo Evaluation In the Mouse Disease Modelmentioning
confidence: 99%
“…However, given the emergence of more contagious and potentially pathogenic variants, and the need for more effective therapies for patients, the search for new therapeutics remains a priority (7,8). These efforts were launched by a series of repurposing screens of varying sizes.…”
Section: Introductionmentioning
confidence: 99%